Strategi Komunikasi Persuasif Humas Palang Merah Indonesia di Masa Pandemi Covid 19 - Fahri Habibi; Reza Aprianti; Miftah Farid (Tabayyun: Journal of Journalism, 2022)
This research is entitled "PMI Public Relations Persuasive Communication Strategy in Disseminating Public Awareness of Donating Blood During the Covid 19 Pandemic" (Case Study of the Indonesian Red Cross, Palembang City). The purpose of this study was to determine the persuasive communication strategy of PMI Public Relations in disseminating public awareness of blood donation during the COVID-19 pandemic at PMI Public Relations in Palembang. The research method used is descriptive qualitative. Data collection techniques are observation, interviews and documentation. The primary data source of this research is through interviews with the Public Relations Officer of the PMI Palembang City concerned and the people in the city of Palembang. The secondary data sources are in the form of official documentation of PMI Public Relations in the city of Palembang, journals and books. The theory used is source credibility theory. This theory explains that a persuasion activity (persuade) begins with attracting attention or attention and ends with action. The result of this study is the Persuasive Communication Strategy applied by the PMI Public Relations of Palembang city in disseminating public awareness of blood donation during the covid 19 pandemic, which can be described by providing information about blood donation through social media or offline advertising by distributing brochures or installing These banners on the side of the road will attract attention from the process of persuasive communication strategy for PMI Public Relations in Palembang.